ORDINARY KRIGING AND INVERSE-SQUARE-DISTANCE IN ESPACIALIZATION IN THE CHEMICAL ATTRIBUTES OF THE ULTISOL - SOUZA, Gustavo Soares de; LIMA, Julião Soares de Souza; XAVIER, Alexandre Cândido; ROCHA, Wadson Sebastião Duarte da (Scientia Agraria, 2010)
One of the factors that influence the implementation and use of precision agriculture is the accuracy with which the maps of spatial distribution of soil attributes are produced in the process of interpolation of data. The objective was to compare the efficiency of the interpolation of data through the ordinary kriging (Kri) and of the inverse square of the distance (ISD) in the estimate of chemical attributes in the soil. The experiment was installed in the central part of a hillside, in the municipality of Alegre (ES), on an Ultisol Red-Yellow, with loamy texture, where a grating of soil sampling was used containing 128 points, spaced 10 m for analysis of the attributes chemical pH, H+Al and SB. The geostatistics analysis showed that all of the chemical attributes of the soil presented spatial dependence. It was noticed a larger difference look among the maps interpolated by Kri and ISD for the attribute SB, presenting the map interpolated by ISD a larger variability, result of a smaller uniformity of the ash tones. The interpolation methods were efficient in the inference of data for the three analyzed chemical attributes. The interpolation methods used didn't present significant differences, through the analysis of the mistakes of the estimate.